The Role of Big Data in Development of E-Government and Dangers to Privacy - Irfan Rashid (Universitas Komputer Indonesia, 2026)
This paper explores Big Data's central role in shaping E-Government systems and addresses the associated privacy risks. While integrating Big Data in public sectors enhances decision-making, service delivery, and transparency, it simultaneously raises concerns regarding personal data security, surveillance, and privacy invasion. This study critically evaluates the ethical and privacy consequences for citizens alongside the benefits of enhanced governance. Findings indicate that increased transparency, stringent data protection, and robust regulatory frameworks are essential for establishing public trust in E-Government initiatives. Ultimately, the research emphasizes the necessity of balancing Big Data's utility with strong security measures to ensure the long-term sustainability of digital governance